Voice Onset Time in Children - Kushal Raj P; Nataraja NP (Journal of All India Institute of Speech and Hearing, 1970)
The present study reports  VOT for stop  consonants  \p\, \t\  and \k\  in children. 100  male and female children belonging  to 5   age groups, ranging from  4-12  years   were  used  to  elicit 3  sentences as   responses to  3  picture  cards.  The  sentences  elicited as  responses  consisted  of the consonants  /p/ and \k\  in  initial position  and  /t/  in medial position  of the words. These were analyzed using High Resolution   Signal  Analyzer (B and  K 2033) to obtain  VOT. The  results  showed  that  there  was no significant  difference  in VOT  between   males   and   females. Between different age groups of the same sex,  except for  the  children  of 4-5  years, no other  group  had  shown  significantly  different  VOT values.